Decentralised innovation systems and poverty reduction: experimental evidence from Central Africa - Pamuk, Haki; Bulte, E.; Adekunle, A.; Diagne, A. (Oxford University Press, 2015)
We use experimental data to investigate whether a decentralised approach to promoting innovation in central African agriculture outperforms conventional extension ap proaches. Our main result is that this decentralised approach, based on so-called innova tion platforms, is effective in reducing poverty – more effective than conventional extension approaches. However, we also document considerable heterogeneity in terms of platform performance.